KUALITAS BIOPELLET LIMBAH SEKAM PADI (Oryza sativa) SEBAGAI SALAH SATU SOLUSI DALAM MENGHADAPI KRISIS ENERGI - Diana Ulfa; Lusyiani Lusyiani; Gusti A.R. Thamrin (Lambung Mangkurat University-Indonesia, 2021)
The purposes of this study were: 1) To analyze the characteristics of rice husk waste biopellets such as moisture content, density, ash content, flight substance content, calorific value and bound carbon content, 2) To identify the factors that influence the production of biopellets from rice husk waste. This study used a completely randomized design model with 2 (two) factors, namely variations in mesh size and variations of adhesive with 3 (three) replications. Making biopellet samples and testing the characteristics of rice husk biopellets were carried out at the Forest Products Technology Laboratory, Faculty of Forestry, Lambung Mangkurat University, Banjarbaru. The size of the powder and the amount of added adhesive as well as the interaction between the two did not have a significant effect on the value of moisture content, density, ash content, flight substance content and bonded carbon content, but had a very significant effect on heating value. The average value of moisture content ranged from 13.0771 - 14.5932%, the average density value ranged from 0.7698 g/cm3- 0.9548 g/cm3, the average value of the resulting ash content ranged from 16.5233% - 19.9633%, the average value of flying substances ranged from 57.3533% - 63.6067%, the average value of bound carbon was 6.3462% - 8.7668%, and the average heating value ranged from 2781.3800 cal/g - 3378.4600 cal/g. The factors that affect the quality of the biopelet are the process of pretreating the raw material, refining the size and mixing the adhesive.